Cystic fibrosis genetic counselling: an audit of counsellees and their at-risk relatives - Macaulay, Shelley (My University, 2009)
ABSTRACT Cystic fibrosis (CF) is an autosomal recessive disorder that occurs in all ethnic groups. Mutations in the cystic fibrosis transmembrane regulator (CFTR) gene are responsible for pulmonary obstruction, chronic lung infections, pancreatic insufficiency, meconium ileus, failure to thrive and infertility. Genetic testing for CF at the DNA level is available. A diagnosis of CF in an individual has implications for other family members and so genetic counselling should form part of CF management. Genetic counselling has been offered by the Clinical Unit of the Division of Human Genetics, National Health Laboratory Service and the University of the Witwatersrand, Johannesburg, for many years. At the beginning of 2006, genetic services were introduced into the CF Clinics of Johannesburg Hospital by way of specialist Genetic Counselling Clinics. The study aimed to determine who utilises the CF genetic counselling services and why, to estimate the number of at-risk relatives per family, and how many of them had mutation testing and genetic counselling. Finally, the study explored what impact the specialist Genetic Counselling Clinics had on the overall service of genetic counselling. The files of 153 families seen for CF genetic counselling from 1990 to 2006 were analysed. The majority of counsellees (93%) were white. Most counsellees were parents of CF probands (35%). Relatives with carrier risks of 67% (siblings) and 50% formed only 7% and 6% of all counsellees respectively. Most individuals attended genetic counselling in order to gather information. On average, 5.9 ± 3.45 families were seen for CF genetic counselling per year from 1990 to 2005, whereas in 2006, 58 families were seen. Paediatrician, physician and nurse referrals increased notably during 2006 compared to prior years. In 140 unrelated CF-affected families, 1991 at-risk relatives, with carrier risks above 25%, were identified. Only 11% of these relatives had mutation testing and only 8% attended genetic counselling. Uptake of genetic counselling is greater when the service is integrated into CF treatment clinics than when it is offered externally. The low uptake of mutation testing and genetic counselling by at-risk relatives suggests that new methods of educating individuals for cascade screening and testing are required.
Keywords: cystic fibrosis; genetic counselling